Advancements in Proton Exchange Membrane Fuel Cells Improving Efficiency and Durability - Kumar Rakesh; Prabakaran A.; Gaigole P.M.; Esakkiammal U.; N Divya; Sherje Nitin; Ragu Nathan S. (E3S Web of Conferences)
This study analyzes recent improvements in Proton Exchange Membrane Fuel Cells (PEMFCs), concentrating on enhancing their efficiency and durability—two essential aspects for their broad use in clean energy applications. Key advancements include the creation of high- performance catalysts, better membrane materials, and innovative system topologies that dramatically raise fuel cell efficiency. Additionally, this study analyzes techniques to increase PEMFC durability, such as enhanced temperature control, innovative materials that resist deterioration, and operating procedures that boost long-term stability. The results reveal major increases in both efficiency and durability, placing PEMFCs as a viable alternative for sustainable energy generation. By addressing existing obstacles and outlining future research paths, this study adds to the ongoing efforts to develop PEMFC technology, opening the road for its integration into multiple energy systems, including transportation, stationary power, and portable applications.